Exploring Child Rights and the Concept of Childhood in Islam: A Contemporary Descriptive Analysis - Mohammed Houmine; Khadija Loudghiri (Khazanah Hukum, 2023)
This study delves into the realm of children's rights and the concept of childhood, comparing Occidental research spanning the last century and the first two decades of this century with the role of Islam and Islamic civilization in safeguarding these rights. Through an examination of Sharia sources, relevant books, and articles, a descriptive analysis method is employed to uncover the presence of child rights notions and childhood concepts in Islamic references. The findings showcase Islam's robust emphasis on children's rights across various dimensions and the recurrent presence of childhood in diverse sources. Moreover, the study reveals a misrepresentation by certain Western authors regarding the historical trajectory of child rights and childhood within the Islamic framework. In essence, this research underscores Islam's significant contributions to nurturing child rights and advancing the notion of childhood, shedding light on an often underexplored aspect of Islamic civilization.